Ultra-low Fouling and Functionalizable Surface Chemistry Based on Zwitterionic Carboxybetaine Random Copolymers - Lin, Xiaojie (Langmuir, 2018)
Here, we report a simple, yet effective surface modification approach to impart hydrophobic surfaces with super-hydrophilicity using ultra-low fouling/functionalizable carboxybetaine (CB) copolymers via a dip-coating technique. A new series of CB random copolymers with varying amphiphilicities were synthesized and coated on hydrophobic polypropylene (PP) and polystyrene (PS) surfaces. Nonfouling capability of each coating was screened by enzyme-linked immunosorbent assay (ELISA), and further comprehensively assessed against 100% human serum by Micro BCA protein assay kit. The random copolymer containing ~30 mol% of CB unit showed superhydrophilicity with the highest air contact angle of more than 165° in DI water and the best nonfouling capability against 100% human blood serum. Surfaces of a 96-well plate coated with the optimal CB random copolymer showed significantly better nonfouling capability than those of a commercial 96-well plate with an ultra-low attachment surface. Adhesion of mouse embryonic fibroblast cells (NIH3T3) was completely inhibited on surfaces coated with CB random copolymers. Furthermore, the optimal nonfouling CB copolymer surface was functionalized with an antigen via covalent bonding where its specific interactions with its antibody were verified. Thus, this CB random copolymer is capable of imparting both ultra-low fouling and functionalizable capabilities to hydrophobic surfaces for blood-contacting devices.